2022
DOI: 10.1021/acs.jafc.2c00642
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of Stearoyl-CoA Desaturase 1 Decreased Milk Fat and Unsaturated Fatty Acid Contents of the Goat Model Generated by CRISPR/Cas9

Abstract: Goat milk contains a rich source of nutrients, especially unsaturated fatty acids. However, the regulatory mechanism of milk fat and fatty acid synthesis remains unclear. Stearoyl-CoA desaturase 1 (SCD1) is the key enzyme catalyzing monounsaturated fatty acid synthesis and is essential for milk lipid metabolism. To explore milk lipid synthesis mechanism in vivo, SCD1-knockout goats were generated through CRISPR/Cas9 technology for the first time. SCD1 deficiency did not influence goat growth or serum biochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…NaAc ( Figures 1C , D ), sodium propionate ( Figures 1F , G ), but not sodium butyrate ( Figures 1I , J ) significantly increased the phosphorylation level of ERK at the concentration of 0.75 mM ( p < 0.05). Previously study found GPCR-regulated cellular cAMP involved in the modification of mTORC1 activity, which is a crucial pathway for milk synthesis ( 26 ). Activation of G αi protein could inhibit AC (adenylate cyclase) from converting ATP into cAMP, then inhibit the phosphorylation of CREB.…”
Section: Resultsmentioning
confidence: 99%
“…NaAc ( Figures 1C , D ), sodium propionate ( Figures 1F , G ), but not sodium butyrate ( Figures 1I , J ) significantly increased the phosphorylation level of ERK at the concentration of 0.75 mM ( p < 0.05). Previously study found GPCR-regulated cellular cAMP involved in the modification of mTORC1 activity, which is a crucial pathway for milk synthesis ( 26 ). Activation of G αi protein could inhibit AC (adenylate cyclase) from converting ATP into cAMP, then inhibit the phosphorylation of CREB.…”
Section: Resultsmentioning
confidence: 99%
“…Even when the diet was supplemented with high levels of MUFA, decreasing SCD activity seemingly decreased lipid accumulation by limiting the supply of endogenously synthesized MUFAs [ 43 ]. There is ample evidence indicating that SCD can influence the partitioning of fatty acids into and out of neutral lipid species, which is essential in lipid metabolism and body weight control [ 44 , 45 ]. SCD is emerging as a potential therapeutic target for treating obesity, diabetes, and other metabolic diseases [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the gene expression of SCD1 was upregulated in the peak lactation period, which was due to its function as a key enzyme in the synthesis of milk fat in mammary glands [ 4 ]. In SCD1-knockout goats, the milk fat percentage was reduced [ 29 ]. As expected, we found that the expression of ACCα, FAS, and SCD1 was upregulated with the addition of acetate.…”
Section: Discussionmentioning
confidence: 99%